ANALISIS POSTKOLONIAL DALAM NOVEL KEMBALI KE DESA KARYA TRI BUDHI SASTRIO - Yuniani, Emi; Yuwono, Yuwono; Mardiana, Ninik (Magistra Andalusia: Jurnal Ilmu Sastra, 2022)
Postcolonial theory is used to examine the novel Back to the Village by Tri Budhi Sastrio. The novel Back to the Village is the story of an innocent village girl named Putu Larasati, a teenager who was snatched away by her youth, then stranded in the Dutch Company barracks and fell into the arms of a Company soldier named Captain Robert van Eyk. This village girl was lucky because the soldier, although at first was a soldier who was a jerk and a hooker, turned out to love her with all her heart and sincerity. The sincerity and loyalty of the soldier who had become her husband was well recorded in the mind of this innocent country girl. Everything becomes beautiful, calm, serene, and peaceful. The method used in this research is descriptive qualitative method using postcolonial theory. The data of this research are excerpts from the description of postcolonial theory in the novel "Back to the Village" by Tri Budhi Sastrio. The data source of this research is the novel "Back to the Village" by Tri Budhi Sastrio published by C.V Jejak Publisher publisher on Jln. Bojonggenteng Number 18, Kec. Bojonggenteng Kab. Sukabumi, West Java First printing December 2018, 188 pages, 14 x 20 cm. Data collection techniques used reading techniques and note-taking techniques. The data that has been obtained is then written on the data card. After the data that are in accordance with the research focus are collected, the data is then analyzed using the postcolonial theory of Edward Said's thinking: politics, culture, resistance. Analysis of postcolonial theory in the novel "Back to the Village" by Tri Budhi Sastrio is based on Edward Said's thoughts: politics, culture, resistance that the contents of the novel from a political point of view of the Dutch government colonizing Indonesia by utilizing Dutch stooges such as village heads and indigenous women including Putu Larasati figure became a shield for Dutch colonial politics. In the cultural field, indigenous people still maintain etiquette and manners in attitude and speech. This can be seen in the character Putu Larasati. In the field of Resistance, indigenous peoples continued to fight and defend their rights which had been colonized by the Dutch colonials. This is reflected in the character Putu Larasati who fights for her rights as a woman and maintains the dignity of her family.